A randomized double-blind clinical trial investigating the effects of ellagic acid on glycemic status, liver enzymes, and oxidative stress in patients with non-alcoholic fatty liver disease - Sara Mighani; Rasoul Samimi; Mohamadreza Rashidi Nooshabadi; Seyed Amir Farzam; Hossein Khadem Haghighian; Maryam Javadi (BMC Complementary Medicine and Therapies)
Abstract Background It seems that oxidative stress is involved in the occurrence and progression of non-alcoholic fatty liver disease (NAFLD). Considering the antioxidant features of Ellagic acid (EA), this study was designed to assess the effect of EA on some biochemical factors in patients with NAFLD. Methods In this clinical trial, 44 patients were selected based on including criteria and randomly received 180 mg of EA per day (n = 22) or placebo (n = 22) for 8 weeks. At the beginning and end of the study, glycemic indices, lipid profiles, liver enzymes, oxidative stress markers, and inflammatory factors were measured. Results At the end of the study, the mean of insulin, insulin resistance (IR), triglycerides (TG), low-density lipoprotein (LDL), aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), malondialdehyde (MDA), and C-reactive protein (CRP) were significantly decreased in the intervention group (P < 0.05). Also, a significant increase in the mean of total antioxidant capacity (TAC) was observed in the EA group (P < 0.05). However, changes in high-density lipoprotein (HDL), total cholesterol (TC), and fasting blood sugar (FBS) were not significant in any of the groups (P > 0.05). Conclusions Based on the results, the present study provided evidence that EA can be used as a supplemental therapy alongside current treatment plans to reduce the complications of NAFLD due to its antioxidant and anti-inflammatory properties. Trial registration This study was prospectively registered at the Iranian Registry of Clinical Trials on the 23th of January 2022 (ID: IRCT20141025019669N21).